Architectural Implications for Dogs: Architectural Implications for Dogs - V.Narad, Anjali; J. Chaudhari, Vaishnavi (International Journal of Scientific Research and Management (IJSRM), 2021)
Dogs are always identified as a subspecies of a wolf, but the history of its existence is still unsolved. Though many researchers stated the origin of dogs came from the wolf fossil found in Europe several years ago. If the history of domestication is analysed, then it can be said that dogs are the first species to be domesticated on the Earth. In the past few decades’ dogs’ evolution and its involvement in humans life is so meteoric that they became a part of our lives. Dog being the most trustworthy and socialised species on this planet made humans to domesticate them in fields for various activities. This became one of the major reasons to boost economy as well as to develop ones physical and mental condition. Similar to the humans, dogs also have a great list of requirements on basis of their physical and psychological conditions which made it possible to design a dwelling for a dogs living. Sir. BRUCE FOGLE in his book “THE DOGS MIND-Understand Your Dogs Behaviour” explained about the anatomy, physiology and the psychology of a dog.Architecture is all about designing a life and this paper would be an endeavour to design spaces for dogs to strengthen their relationship with humans and environment.